PD-1 knockout on cytotoxic primary murine CD8+ T cells improves their motility in retrovirus infected mice - Mittermüller, Daniela; Otto, Lucas; Kilian, Annika Loredana; Schnormeier, Ann-Kathrin; Littwitz-Salomon, Elisabeth; Hasenberg, Anja; Dittmer, Ulf; Gunzer, Matthias (Frontiers in Immunology, 2024)
Cytotoxic T lymphocyte (CTL) motility is an important feature of effective CTL responses and is impaired when CTLs become exhausted, e.g. during chronic retroviral infections. A prominent T cell exhaustion marker is programmed cell death protein 1 (PD-1) and antibodies against the interaction of PD-1 and PD-ligand 1 (PD-L1) are known to improve CTL functions. However, antibody blockade affects all PD-1/PD-L1-expressing cell types, thus, the observed effects cannot be attributed selectively to CTLs. To overcome this problem, we performed CRISPR/Cas9 based knockout of the PD-1 coding gene PDCD1 in naïve Friend Retrovirus (FV)-specific CTLs. We transferred 1,000 of these cells into mice where they proliferated upon FV-infection. Using intravital two-photon microscopy we visualized CTL motility in the bone marrow and evaluated cytotoxic molecule expression by flow cytometry. Knockout of PDCD1 improved the CTL motility at 14 days post infection and enhanced the expression of cytotoxicity markers. Our data show the potential of genetic tuning of naive antiviral CTLs and might be relevant for future designs of improved T cell-mediated therapies.